Functionalization of tannic acid and campesterol with polyelectrolyte multilayer membranes for lithium ions separation and recycling - P. Nikhil Chandra (Elsevier, 2021)
The potential use of chitosan/poly(styrene sulfonate) (CHS/PSS) polyelectrolyte multilayer (PEM) membranes functionalized with tannic acid (TA) and campesterol (CHT) for efficient separation and recycling of lithium from aqueous matrix under ultrafiltration conditions are examined. The PEM assembled via layer by layer (LbL) method accelerates the recycling process of lithium as it efficiently separates the metal complexed larger molecules. A total of eight CHS/PSS bilayers were sufficient for the effective lithium recovery. The microscopic studies confirmed the surface morphological change of PEM from smooth to rough after immobilization (MIUF). The successful immobilization of TA and CHT into PEMs are illustrated using spectroscopic studies. The TA and CHT assisted separation (MEUF) are also carried out by complexation of metal solution prior to filtration. The assisted mode provides a very good recovery of >94% with a excellent permeate flux of 1.25 m3/m2 day and 1.96 m3/m2 day for TA and CHT respectively. The recycling of lithium ions from water matrix is experimented with different parameters and experimental conditions. The reusability and extended life of the membrane systems indicate its potential in small scale filtration units.